Emergence of Nontrivial Low‐Energy Dirac Fermions in Antiferromagnetic EuCd2As2. Issue 14 (24th February 2020) - Ma, Junzhang; Wang, Han; Nie, Simin; Yi, Changjiang; Xu, Yuanfeng; Li, Hang; Jandke, Jasmin; Wulfhekel, Wulf; Huang, Yaobo; West, Damien; Richard, Pierre; Chikina, Alla; et al.
Abstract: Parity‐time symmetry plays an essential role for the formation of Dirac states in Dirac semimetals. So far, all of the experimentally identified topologically nontrivial Dirac semimetals (DSMs) possess both parity and time reversal symmetry. The realization of magnetic topological DSMs remains a major issue in topological material research. Here, combining angle‐resolved photoemission spectroscopy with density functional theory calculations, it is ascertained that band inversion induces a topologically nontrivial ground state in EuCd2 As2 . As a result, ideal magnetic Dirac fermions with simplest double cone structure near the Fermi level emerge in the antiferromagnetic (AFM) phase. The magnetic order breaks time reversal symmetry, but preserves inversion symmetry. The double degeneracy of the Dirac bands is protected by a combination of inversion, time‐reversal, and an additional translation operation. Moreover, the calculations show that a deviation of the magnetic moments from the c ‐axis leads to the breaking of C3 rotation symmetry, and thus, a small bandgap opens at the Dirac point in the bulk. In this case, the system hosts a novel state containing three different types of topological insulator: axion insulator, AFM topological crystalline insulator (TCI), and higher order topological insulator. The results provide an enlarged platform for the quest of topological Dirac fermions in a magnetic system. Abstract : When magnetism meets topology, colorful novel states can be created in materials. The realization of magnetic topological Dirac materials remains a major issue in topological physics studies. In this work, it is ascertained that the topologically nontrivial ground state of EuCd2 As2 is a good candidate for different types of magnetic topological state: magnetic topological Dirac semimetal, axion insulator, antiferromagnetic TCI, and higher order topological insulator.